AN ANALYSIS OF TRANSLATION SHIFT ON VERB PHRASES IN ENGLISH-INDONESIAN TRANSLATION OF SURAH YASEEN (CHAPTER 36) - Asmanah Asmanah; Wiki Tedi Rahmawati; Linda Astuti Rangkuti (English Education Study Program FKIP Universitas Alwashliyah Medan, 2021)
The aims of this study were to find out the types and the dominant type of translation shift on verb phrases used in English-Indonesian translation of Surah Yaseen (Chapter 36). This study was conducted by using descriptive qualitative method. The data were the verb phrases in English-Indonesian translation of Surah Yaseen. The data were collected and analyzed by comparing, classifying, categorizing, describing, calculating, and displaying by using table. The result of this study found there were three types of translation shift on verb phrases in English-Indonesian translation of Surah Yaseen namely: class shift (51.25%), level shift (43.75%), and structure shift (5%). The most dominant type of translation shift used was the class shift.